Design, synthesis, characterization and evaluation of Chitosan-based hydrogel for controlled drug delivery system - Safari, Justin Bazibuhe (Rhodes University, Faculty of Science, Department of Chemistry)
Hepatitis B infection is a deadly infectious disease caused by the hepatitis B virus and is responsible for many deaths every year worldwide. Despite medication and vaccines against hepatitis B infection, it still presents high morbidity and mortality among populations. This is partly due to factors such as a long medication period of the existing treatments, resulting in poor patient compliance and leading to treatment failure. In addition, this situation can be responsible for the observed emerging drug resistance. Hence, novel drugs and drug delivery systems are needed to tackle this matter. Many strategies have been used to develop long-acting drug delivery systems treatment for several infectious diseases. Hydrogel drug delivery systems have shown interesting results as controlled drug delivery systems for several drugs. Therefore, the present study aimed to develop chitosan grafted poly (acrylamide-co-acrylic acid) hydrogel and apply it as a pH-sensitive controlled delivery system of tenofovir disoproxil fumarate (TDF). TDF is a nucleoside reverse transcriptase inhibitor used as first-line treatment of hepatitis B chronic infection and in the treatment of other viral infections. The free-radical polymerization method was utilized to modify chitosan by grafting acrylamide and acrylic acid and using N, N'-methylene bisacrylamide as the crosslinking agent to prepare the hydrogel, followed by an optimization of parameters that could affect the swelling capacity. The prepared chitosan-g-poly(acrylamide-co-acrylic acid) hydrogel was characterized using Fourier Transmission Infra-red spectroscopy (FTIR), X-Ray Diffraction (XRD), Thermal Gravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), Energy-dispersive X-ray spectroscopy (EDS), Scanning Electron Microscopy (SEM), and was evaluated for cytotoxicity using a HeLa cell assay. TDF was used as a drug model, it was loaded by the swelling equilibrium method, following by the investigation of the release profile of TDF-loaded hydrogel at pH 1.2 and 7.4. A successful synthesis of chitosan grafted poly(acrylamide-co-acrylic acid) hydrogel was confirmed by Fourier Transmission Infra-red spectroscopy (FTIR), X-Ray Diffraction Spectroscopy (XRD), Thermal Gravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), Energy-dispersive X-ray spectroscopy (EDS) and Scanning Electron Microscopy (SEM). Optimization results showed that the ratio of monomers impacted the swelling ratio of the hydrogel and both the concentration of the crosslinking agent, and the reaction initiator also affected the swelling ratio. The synthesized hydrogels were sensitive to pH and ionic strength. Hydrogel swelling was lower in acidic solutions and higher in neutral and basic solutions and decreased with the increasing ionic strength. Furthermore, SEM results revealed that hydrogel have a rough and fibrous surface structure with numerous pores. Cytotoxicity studies demonstrated that the hydrogel was non-cytotoxic at 50 Î¼g/ml against HeLa cells which suggested a good biocompatibility of the material. TDF was loaded and released from the hydrogels and showed an encapsulation efficiency and drug loading percentage ranging from 81-96% and 8-10%, respectively. TDF release profile was found to be low in buffer solution of pH 1.2 (in the range of 5-10%) and much higher (38-53%) at pH 7.4 within 96 hours. TDF maintained its chemical integrity after release and the hydrogels can therefore be proposed as a new controlled-release drug delivery system for hepatitis B treatment.
Keywords: Chitosan; Drug delivery systems; Drugs -- Controlled release; Tenofovir; Colloids; Hepatitis B Chemotherapy; Hydrogel